ChemInform Abstract: A Copper‐Catalyzed Coupling Reaction of Vinyl Halides and Carbazates: Application in the Assembly of Polysubstituted Pyrroles. Issue 33 (19th August 2014) - Zhou, Chengang; Ma, Dawei
Abstract More than 70 differently substituted pyrroles are synthesized.